Visual Acuity Thresholds in Preterm Newborns: An Experimental Study - Ruth Batista Bezerra Fagundes; Pedro Ykaro Fialho Silva; Mirella Telles Salgueiro Barboni; Gentil Gomes da Fonseca Filho; Valeria Azevedo de Almeida; Ingrid Guerra Azevedo; Silvana Alves Pereira (MDPI AG, 2024)
Purpose: Visual acuity plays a role in mediating neurological development in infants by enabling the differentiation of shapes and discriminating objects. Given the rapid structural development of the brain in the first days of life, this aspect is particularly significant for preterm infants, who typically experience this developmental phase while hospitalized in the neonatal intensive care unit (NICU). Therefore, this study aimed to assess visual acuity thresholds in preterm infants during hospitalization and to evaluate possible correlations between visual acuity and clinical parameters. Methods: A cross-sectional study was conducted in an NICU in Northeast Brazil. The visual acuity thresholds were tested using the Teller Acuity Cards II, comprised of 17 gray cards, with one 4 mm diameter peephole at the center and presented with about 35% reflectance. Preterm infants were positioned supine, at 30° elevation on the laps of their caregivers. The evaluator presented both sides of the cards and observed the eye fixation and reactions on both sides. Results: A total of 42 preterm infants with corrected gestational age between 30 to 36 weeks and 6 days were included. Visual acuity ranged from 0.23 to 0.64 cycle per degree. The mean visual acuity threshold was 0.32 cycles per degree for preterm infants at around 32 weeks of corrected gestational age. The visual acuity was not correlated with gestational age (p = 0.18), and neither were birth weight (p = 0.83) or duration of respiratory support (p = 0.98). However, days of phototherapy were inversely correlated with visual acuity (p = 0.04). Conclusions: Despite the challenges of hospitalization, it was possible to carry out a psychophysical test to assess visual acuity in preterm infants. The visual acuity showed no correlation with clinical parameters such as gestational age, birth weight, and duration of respiratory support. However, there was an inverse correlation between the number of days in phototherapy and visual acuity. Understanding the visual acuity levels in preterm infants during their NICU stay can contribute to tailoring interventions and care strategies that specifically address their visual developmental needs. This knowledge may guide healthcare professionals in optimizing the NICU environment to provide appropriate visual stimuli that support neurological development.